A Study on the Artistic Value of Dai Fitness Dance from the Perspective of Dance Ecology - Liu, Jiayu; Phuchomsri, Sarawadee; Kotchapakdee, Pat (Journal of Ecohumanism, 2024)
This study, through the lens of dance ecology, deeply analyzes the artistic value of Dai fitness dance and explores its historical background, cultural connotations, and its current development in modern society. The research reveals that Dai fitness dance is not only a form of cultural expression but also carries multiple functions such as ethnic identity, social interaction, and personal health.The Dai fitness dance holds significant artistic value across multiple dimensions such as aesthetics, cognition, society, fitness, inheritance, and dissemination. Through the framework of dance ecology, this study explores the performance of the Dai fitness dance in different cultural and social environments, analyzes its potential and challenges for future development, and further provides a theoretical basis for the protection and innovation of ethnic dance culture.